(untitled) (Abril – NEPA / UFF, 2018)
This article analyses some of the linguistic and literary strategies used by Ana Paula Tavares2 to describe the spiritual discourse of Bantu derivation in the chronicle (crônica) “O cesto de adivinhação”, taken from the book A cabeça de Salomé (2004)3. I will argue that, in this text, Tavares expresses the importance of spiritualism through the use of culture-bound terms, as well as the deployment of stylistic strategies, in order to redefine the Angola identity. The result of such literary creativity, matched with a deep historical and ethnographic investigation of the Bantu populations represented in her fictional work, supports the recreation of the Angolan identity that puts a great emphasis on aspects such as rituals, ancestral characters, and key figures that represent the culture of the native societies of the country. The aim is to discuss the ideological tensions and contradictions existing in Angola, as well as to inform and inspire a different perspective towards its multicultural society, through the words of the above author. ———————————————————————————— O ESPIRITUALISMO BANTU EM “O CESTO DE ADIVINHAÇÃO” DE ANA PAULA TAVARES O presente artigo pretende analisar as estratégias linguísticas e literárias utilizadas por Ana Paula Tavares para descrever o espiritualismo de origem bantu na crônica “O cesto de adivinhação”, que faz parte da coletânea A cabeça de Salomé (2004). Pretende-se demontrar que, no texto mencionado, Tavares discute sobre a importância do espiritualismo como parte de um processo de formação identitária do país angolano, através de termos e de certas expressões literárias específicas. A criatividade literária da autora, enriquecida por uma investigação histórica e etnográfica das populações bantu representadas na própria obra ficcional, suporta a criação de uma identidade angolana que enfatiza a importância dos rituais, das personagens ancestrais e das personalidades que representam a cultura das sociedades nativas do país. O objetivo é discutir as tensões ideológicas e as contradições que existem em Angola, além de informar e encorajar uma perspectiva diferente perante a sociedade multicultural angolana, analisando a escrita da autora. — Artigo em inglês. — DOI: http://dx.doi.org/10.22409/abriluff2018n21a518.